Екстрагування біологічно активних речовин з біомаси Gladiolus imbricatus, культивованої в умовах in vitro - Крвавич, Анна Сергіївна (Національний університет "Львівська політехніка", 2016)
Дисертаційна робота присвячена дослідженню процесу культивування Gladiolus imbricatus в умовах in vitro, а також механізму та кінетики процесу екстрагування БАР з дикорослої сировини та з культивованої калусної біомаси. Показана залежність процесу екстрагування цільових компонентів від розміру частинок та температури проведення процесу.На основі розв’язання математичної моделі та експериментальних даних кінетики екстрагування БАР з дикорослого виду та культивованого Gladiolus imbricatus в умовах in vitro отримано значення коефіцієнту дифузії Dм. Запропоновано технологічну схему процесу екстрагування БАР з культивованої біомаси. Запропоновано принципову технологічну та апаратурно-технологічну схеми виробництва екстракту біомаси. Дана технологія може бути рекомендована для виробництва БАР для косметичної, хімічної та інших галузей промисловості. Диссертационная работа посвящена исследованию процесса культивирования Gladiolus imbricatus в условиях in vitro, а также механизма и кинетики процесса экстрагирования БАВ из дикорастущего сырья и из культивируемой биомассы. Показана зависимость процесса экстрагирования целевых компонентов от размера частиц и температуры проведения процесса. На основе решения математической модели и экспериментальных данных кинетики экстрагирования БАВ из дикорастущего вида и культивованого Gladiolus imbricatus в условиях in vitro получено значение коэффициента диффузии Dм. Предложена технологическая схема процесса экстрагирования БАВ из культивируемой калусной биомассы. Предложена принципиальная технологическая и аппаратурно-технологическая схемы производства экстракта биомассы. Данная технология может быть рекомендованная для производства БАВ для косметической, химической и других отраслей промышленности. This dissertation is dedicated to research of the cultivation process of Gladiolus imbricatus in vitro conditions and besides to the kinetics mechanism and process of the extraction of BAC from wild-breed raw species and cultivated callus biomass. As a result of reduction of natural supplies of medical plants, perspective is an alternative biotechnological method of production of biologically active compounds from the in vitro culture. That is why the introduction to the in vitro culture of Gladiolus imbricatus and the comparative analysis of BAC the presence of in extracts of herbs and сallus mass is important scientific practical problem. The dependence of the extraction process of target components from the particle size and the temperature of the process conduction has been shown. It has been shown that the process of BAC extraction from wild species is very slower with increasing particle and limited by inner diffusion. The process runs by the mixed mechanism (external and inner diffusion) in case of extraction from ground particle and mixed conditions. Optimum conditions of extraction conduction process of BAS have been established. The resulting ethanolic and water extracts was filtered and concentrated and then tested for various BAC by conventional methods – polysaccharides, flavonoids and glycosides, terpenoids, vitamin C, aromatic and quinones compounds were commonly found. Different phytochemicals have been found to possess a wide range of activities, which may help in protection against chronic diseases. For example, flavonoids have been reported to have antiviral, anti-allergic, anti-platelet, anti-inflammatory and antitumor activities. Based on the mathematical extracting and experimental data of BAC extraction kinetics from wild-breed species and cultivated Gladiolus imbricatus in vitro conditions the diffusion coefficient values Dм has been obtained. Mathematical models that give the opportunity to identify existence of different target components extraction mechanisms from porous structures have been presented and determine the whole process speed: a) inner diffusion mechanism; b) external diffusion mechanism; c) mixed diffusion mechanism; d) mixed diffusion chemical interaction mechanism. The optimum cultivation parameters of Gladiolus imbricatus in vitro conditions in the laboratory terms (both shallow and deep method) have been established. The material balance process has been compiled and on its basis the indicators for zooming process in the bioreactor terms have been calculated. The fundamental technology and hardware-technological scheme of biomass extract production have been suggested. This technology could have been recommended for the production of BAC for the cosmetics, chemical and other industries.
Экстрагирование биологически активних соединений с биомассы Gladiolus imbricatus, культивированной в условиях in vitro
The extraction of biologically active substance from biomass of Gladiolus imbricatus obtained in vitro cultivation
Keywords: Gladiolus imbricatus; біологічно-активні речовини; ферментер; кінетика процесу; екстрагування цільових компонентів; Gladiolus imbricatus; биологически-активные вещества; ферментер; кинетика процесса; экстрагирования целевых компонентов; Gladiolus imbricatus; biologically active substance; fermenter; process kinetics; extraction of target components